Iraq Government Excavations at ‛Aqar Qūf. Third Interim Report, 1944-5 - Baqir, Taha
Programme for the New Season — The Central Building — Stratigraphie Check — Outlying Units and Other Soundings — The Painted Palace — Ramps and Stairway Constructions — Conclusion in Regard to Stratification — Objects — Stairways of the Ziggurat (Mohammad Ali Mustafa).